Immunological alterations due to hemodialysis might interfere with early complications in renal transplantation - Mai, Kristin; Kirschfink, Michael (Analytical cellular pathology, 2019)
Background. Chronic or intercurrent alterations of the immune system in patients with end-stage renal disease (CKD) and intermittent hemodialysis (CKD5D, HD) have been attributed to an acute rejection of renal allograft. Methods. Leukocyte subsets in flow cytometry, complement activation, and concentrations of TGFβ, sCD30 (ELISA), and interleukins (CBA) of fifteen patients eligible for renal transplantation were analyzed before, during, and after a regular HD. Results. Before HD, the median proportion of CD8
Gesehen am 28.05.2019